Afrosalsola (Amaranthaceae-Chenopodiaceae), an intermediate C3-C4 lineage from NW Africa and the Canary Islands, and some new combinations in African species of Caroxylon and Soda - Akhani, Hossein; Abdullahi, Hussaini; Rudov, Alexander (Mediterranean Botany, 2024)
The segregation of the polyphyletic genus Salsola (Amaranthaceae-Chenopodiaceae) caused enormous nomenclatural changes during the last two decades. A lineage, that is still awaiting to be validated by a new valid name comprises four interesting taxa endemic to the Canary Islands and NW Africa. These are shrubby plants with opposite and alternate branches and leaves, specific leaf-anatomy with a hypodermis and Kranz-like cells performing a C3-C4 intermediate photosynthetic pathway (C2 type). The new genus Afrosalsola is described with the inclusion of 2 species [Afrosalsola divaricata (Mass. ex Link) Akhani comb. nov., and A. deschaseauxiana (Litard. & Maire) Akhani comb. nov.] and three subspecies of the former [Afrosalsola divaricata subsp. divaricata, A. divaricata subsp. verticillata (Schousboe) Akhani and A. divaricata subsp. gymnomaschala (Maire) Akhani]. The synonymy of Salsola deschaseauxiana Litard. & Maire with S. verticillata Mass. ex Link is rejected based on typical alternate leaves of the former. Salsola divaricata is typified based on its original collection in BM. Additional new combinations of African species belonging to Caroxylon and Soda are provided.